2022
DOI: 10.1371/journal.pone.0271901
|View full text |Cite
|
Sign up to set email alerts
|

OX2R-selective orexin agonism is sufficient to ameliorate cataplexy and sleep/wake fragmentation without inducing drug-seeking behavior in mouse model of narcolepsy

Abstract: Acquired loss of hypothalamic orexin (hypocretin)-producing neurons causes the chronic sleep disorder narcolepsy-cataplexy. Orexin replacement therapy using orexin receptor agonists is expected as a mechanistic treatment for narcolepsy. Orexins act on two receptor subtypes, OX1R and OX2R, the latter being more strongly implicated in sleep/wake regulation. However, it has been unclear whether the activation of only OX2R, or both OX1R and OX2R, is required to replace the endogenous orexin functions in the brain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
1
8
0
1
Order By: Relevance
“… 19 Other preclinical studies indicate that although OX2R play the more prominent role in the orexin modulation of wake-sleep states, OX1R are also relevant to the physiological control of REM sleep and vigilance-state related muscle tone and to the promotion of arousal. 42 , 44 , 45 Nevertheless, recent work demonstrated that pharmacological OX2R agonism is sufficient to ameliorate cataplexy and sleep/wake fragmentation in orexin KO mice 46 and in orexin-neuron deficient orexin-ataxin 3 mice. 47 This discrepancy awaits clarification.…”
Section: The Biology Of Orexinsmentioning
confidence: 99%
“… 19 Other preclinical studies indicate that although OX2R play the more prominent role in the orexin modulation of wake-sleep states, OX1R are also relevant to the physiological control of REM sleep and vigilance-state related muscle tone and to the promotion of arousal. 42 , 44 , 45 Nevertheless, recent work demonstrated that pharmacological OX2R agonism is sufficient to ameliorate cataplexy and sleep/wake fragmentation in orexin KO mice 46 and in orexin-neuron deficient orexin-ataxin 3 mice. 47 This discrepancy awaits clarification.…”
Section: The Biology Of Orexinsmentioning
confidence: 99%
“…En effet, l'administration systémique d'hypocrétine chez le chien narcoleptique [38], l'injection intra-cérébro-ventriculaire d'hypocrétine chez des souris Orexine/Ataxine 3 [39], la mise en place de greffons de neurones à hypocrétine chez des souris Orexine/Ataxine3 [40], ou encore l'infusion intrathécale d'hypocrétine chez des souris Orex-KO [41] suppriment les cataplexies. Les injections intrapéritonéales ou intra-cérébro-ventriculaires d'agonistes non-peptidergiques des récepteurs 2 à hypocrétine (YNT-185 et AL-OXB) permet également une réduction des cataplexies chez les souris Orex-KO et Orexine/Ataxine3 [42,43]. Le lien physiopathologique entre l'hypocrétine et la cataplexie est donc bien établi.…”
Section: Iii-hypocrétine Et Cataplexieunclassified
“…Moreover, 8 was obtained from the hydrogenation of amide 10. The other cinnamoyl derivatives (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were synthesized in the same manner as 10, using the corresponding amines. The solid-state structure of 18 was determined unequivocally using single-crystal X-ray diffraction analysis (for details, see the Supporting Information).…”
Section: Synthetic Chemistry and Eutomer Determinationmentioning
confidence: 99%
“…35 Moreover, our group has recently reported that the OX2R-selective peptide AL-OXB does not show any preference in a conditioned place-preference (CPP) test. 14 However, the direct involvement of receptor-selective activation in the reward system has not yet been investigated using selective smallmolecule agonists. Thus, we first performed a CPP test using the OX1R-selective agonist (R)-18, OX2Rselective agonist (S)-2, and OX1R/OX2R dual agonist (R)-2 to clarify the involvement of OX1R-selective activation in the reward system.…”
Section: Synthetic Chemistry and Eutomer Determinationmentioning
confidence: 99%
See 1 more Smart Citation